2010
DOI: 10.1038/ki.2010.314
|View full text |Cite
|
Sign up to set email alerts
|

Association of soluble CD89 levels with disease progression but not susceptibility in IgA nephropathy

Abstract: The Fc-α receptor (FcαR/CD89) is involved in IgA complex formation and may affect the development of IgA nephropathy (IgAN). In this study, we tested the genetic variations of the CD89 gene in relation to disease susceptibility in IgAN and the expression of soluble CD89 (sCD89) in sera of patients with IgAN and in controls. There was a significant difference between the levels of sCD89-IgA complexes, measured by sandwich enzyme-linked immunosorbent assay (ELISA), in 177 patients with IgAN with and without dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 76 publications
1
58
2
1
Order By: Relevance
“…An association between the levels of sCD89-IgA complexes in serum and the severity of IgAN has been observed. 104 Specifically, patients with IgAN without disease progression had high levels of sCD89 in contrast to low levels of sCD89 in the disease progression group, suggesting that sCD89-IgA complexes may be protective. In contrast, an animal model suggested that interaction between four entities-Gd-IgA1, sCD89, transferrin receptor, and transglutaminase 2 in mesangial cells-is needed for disease development.…”
Section: Resultsmentioning
confidence: 99%
“…An association between the levels of sCD89-IgA complexes in serum and the severity of IgAN has been observed. 104 Specifically, patients with IgAN without disease progression had high levels of sCD89 in contrast to low levels of sCD89 in the disease progression group, suggesting that sCD89-IgA complexes may be protective. In contrast, an animal model suggested that interaction between four entities-Gd-IgA1, sCD89, transferrin receptor, and transglutaminase 2 in mesangial cells-is needed for disease development.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, cleavage of the extracellular domain of FcaRI is induced, leading to the formation of circulating IgA/FcaRI immune complexes, which are found in mesangial deposits. IgA/FcaRI immune complexes have been implicated in disease exacerbation through the release of pro-inflammatory cytokines, secretion of chemokines and the resultant migration of macrophages into the kidney [40,[89][90][91].…”
Section: Anti-glycan Antibodies and Immune Complexesmentioning
confidence: 99%
“…The increase of IgA-soluble CD89 (sCD89) complexes in the serum of patients with IgAN has been reported [18,27]. However, the exact role of sCD89 in mesangial IgA1 deposit formation and disease progression remains indefinite and could involve an interaction with the TfR and other unknown molecular mechanisms.…”
Section: Pathophysiology (Figure 1)mentioning
confidence: 97%
“…An association between the serum levels of sCD89-IgA complexes and the severity of IgAN has been reported. The single-nucleotide polymorphism rs11084377 is probably one of the genetic regulators of the production or expression of sCD89 [27].…”
Section: Immune Complexesmentioning
confidence: 99%